The effect of corporate credit rating changes on UK common stock returns - Zhang, Huizhong (2020)
Credit ratings play an essential role in the UK financial market, and their changes can convey information to affect the stock returns. This paper studies the impact of corporate credit rating changes on UK stock returns instead of bond rating revisions. We adopt the event study method to analyze 283 samples of corporate credit rating revisions by Standard & Poor`s and Moody`s from 1999 to 2020. Results indicate that significant negative abnormal returns exist in downgrade changes, while the upgrades only have insignificant abnormal returns. The multiple-step and contaminated rating reviews result in a more incredible market reaction than the others. Cross-sectional regressions are launched to investigate whether the switch to and within the investment and speculative category would affect the abnormal returns but only get an insignificant result.